Analisis Total Asset Turnover (TATO), Gross Profit Margin (GPM) dan Return on Investment (ROI) Terhadap Pertumbuhan Laba Pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia - Sutinah Yolanda; Iin Hendrayani (P3M STIE Mulia Darma Pratama, 2019)
The study examines the Total Asset Turnover (TATO), Gross Profit Margin (GPM) and Return on Investment (ROI) analysis of profit growth in the company's industrial sector of consumer goods listed in the Indonesia Stock Exchange. In this study the data used is secondary data that is data directly obtained from the Indonesia stock Exchange. The population number in this research is 42 companies of the consumption industrial goods sector, where the numbers of samples are 14 companies of industrial goods consumption during period 2015-2017. In this study samples were taken using purposive sampling, namely the selection of samples based on the criteria that had been determined by the study. Data analysis in this study is multiple linear analyses. Regression analysis serves to test the influence of independent variables (Total Asset Turnover, Gross Profit Margin and Return on Investment) against dependent variables (profit growth). The partial test result in the study, namely Total Asset Turnover, has significant and negative impact on profit growth, Gross Profit Margin has no effect on profit growth, and independent variable Return on Investment has significant and negative impact against profit growth. Simultaneously, Total Asset Turnover, Gross Profit Margin and Return on Investment affect the growth of profit.